Innovation Practices and Challenges in the Telecommunication Industry: A Roadmap for Value Creation and Sustainable Growth - Hajar M.A.; Al-Sharafi M.A.; Ibrahim N.; Ibrahim D.N.; Al-Matari A.S.; Al-Haimi B.; Al-Tahitah A. (Springer Science and Business Media Deutschland GmbH, 2025)
This study investigates innovation practices within Yemen?s telecommunications industry in the face of rapid technological advances and intense competition. Employing semi-structured interviews with ten key stakeholders, it explores the challenges and proposes a roadmap for success in the sector. The data, analyzed using thematic analysis, revealed four core themes: innovation management and its challenges, the impact of Yemen?s accession to the WTO and market liberalization, the incorporation of value innovation, and future innovation aspirations. These themes were further refined to 19 subthemes. The study, guided by Resource Based View (RBV) theory and Value Innovation logic, emphasizes the role of unique and difficult-to-replicate attributes in cultivating a competitive advantage in a rapidly evolving environment. The insights generated propose a strategic roadmap to strengthen value innovation activities, enhance customer satisfaction and loyalty, and promote company performance and sustainable growth. Despite Yemen?s socioeconomic challenges, the research highlights significant opportunities in the telecommunications sector. The findings provide a useful framework for policymakers and industry stakeholders, illuminating the potential for growth and effective innovation management within Yemen?s telecommunications industry. ? The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.